Implementasi Ajaran Tarekat Naqsyabandiyah Yayasan Jabal Qubis dalam Membina Akhlak Jamaah - Rasella, Rasella; Wiza, Rahmi (TSAQOFAH, 2025)
The moral crisis currently afflicting society has become a serious concern in various aspects of life, including social, cultural, and spiritual dimensions. One approach believed to effectively address this crisis is through moral development based on Sufism teachings, particularly the tariqa (order). This article discusses the implementation of the Naqshbandi teachings of the Jabal Qubis Foundation in nurturing the morals of its congregants. The objective of this research is to understand how the implementation of the Naqshbandi teachings, particularly at the Naqshbandi surau (prayer house) of the Jabal Qubis Foundation, fosters the morals of congregants in Pasaman District. The method employed is qualitative, with data collection techniques including observation, interviews, and documentation. The data sources for this research were obtained from eight informants, consisting of one mursyid (spiritual guide) and seven congregants of the Naqshbandi Foundation. The results of the study indicate that: 1) The application of the tariqa teachings consists of three stages: baiat (initiation), tawajuh (spiritual focus), and suluk (spiritual journey); 2) The challenges faced by the mursyid include the presence of unseen beings within congregants who feel discontent, while challenges from the congregants arise internally, such as laziness in doing good deeds, and externally, including ridicule from family, society, friends, as well as economic factors.